Dose rate effects in the radiation damage of the plastic scintillators of the CMS hadron endcap calorimeter - (:unkn) unknown (IOP PUBLISHING LTD, 2016)
We present measurements of the reduction of light output by plastic scintillators irradiated in the CMS detector during the 8 TeV run of the Large Hadron Collider and show that they indicate a strong dose rate effect. The damage for a given dose is larger for lower dose rate exposures. The results agree with previous measurements of dose rate effects, but are stronger due to the very low dose rates probed. We show that the scaling with dose rate is consistent with that expected from diffusion effects.
Keywords: Radiation damage to detector materials (solid state); Radiation-hard detectors; Scintillators and scintillating fibres and light guides; Calorimeters; STABILITY; RECOVERY; CENTERS